Entity-Relationship Diagram Technique in Database - Palinggi, Owen Baan; Triana, Yaya Sudarya; Permana, Muhamad Bagas; Huda, Darul Fitahul; Priyono, Kus Andi (Journal Collabits, 2024)
The Entity Relationship Diagram (ERD) is one of the most important data modeling techniques in the database design process. ERDs are used to represent data in a conceptual form before being implemented into the actual database schema. By using an ERD, developers can illustrate the relationships between entities, the attributes possessed by each entity, and the types of relationships that occur between these entities.The use of ERDs in database design has several main benefits. First, ERDs help to accurately and consistently model data requirements before the implementation stage. Second, ERDs provide a clear visual representation of the data structure, facilitating communication and understanding among team members. Third, ERDs serve as the basis for designing an efficient and well-structured database schema.Despite being an essential technique, many developers still struggle with creating accurate and appropriate ERDs. Errors in designing ERDs can cause serious problems in database implementation, such as data redundancy, anomalies, or even data loss. Therefore, a deep understanding of the concepts and rules in creating ERDs is crucial.In this journal, an example of a correct ERD will be presented along with a detailed explanation of each entity, attribute, and relationship involved. This discussion is expected to provide guidance for readers in designing accurate ERDs that meet the requirements, thereby producing an efficient database.